Impact bond dataset - Government Outcomes Lab, Blavatnik School of Government (University of Oxford, 2022)
Our Impact Bond Dataset collects data on social impact bond projects. This is the flagship dataset of our INDIGO initiative (International Network for Data on Impact and Government Outcomes). INDIGO is an emerging data collaborative that invites different organisations involved in impact bond projects to share their data with a broader community. Due to the collaborative process that supplies our dataset, data may be incomplete and, in some cases, there is missing data for several variables. We rely on the community of stakeholders to stay up to date with recent developments in the market.